Proceedings of the 2007 ACM Conference on Recommender Systems 2007
DOI: 10.1145/1297231.1297260
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating information presentation strategies for spoken recommendations

Abstract: We report the results of a Wizard-of-Oz (WoZ) study comparing two approaches to presenting information in a spoken dialogue system generating flight recommendations. We found that recommendations presented using the user-model based summarize and refine (UMSR) approach enable more efficient information retrieval than the data-driven summarize and refine (SR) approach. In addition, user ratings on four evaluation criteria showed a clear preference for recommendations based on the UMSR approach.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
17
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 9 publications
2
17
0
Order By: Relevance
“…However, demonstrating perception is in some ways a necessary prerequisite to task-based evaluation: if participants do not notice any difference between the forms of output, it is unlikely to make any great difference to their task performance. A specific instance where the results of an overhearer study agreed with those from a task-based study is found in the pair of FLIGHTS studies mentioned above (Demberg and Moore 2006;Winterboer and Moore 2007).…”
Section: User Evaluation Of Generated Outputsupporting
confidence: 56%
See 4 more Smart Citations
“…However, demonstrating perception is in some ways a necessary prerequisite to task-based evaluation: if participants do not notice any difference between the forms of output, it is unlikely to make any great difference to their task performance. A specific instance where the results of an overhearer study agreed with those from a task-based study is found in the pair of FLIGHTS studies mentioned above (Demberg and Moore 2006;Winterboer and Moore 2007).…”
Section: User Evaluation Of Generated Outputsupporting
confidence: 56%
“…Another possible explanation is that this effect arises from the experimental setting: the subjects were judging appropriateness with reference to a random user model, rather than on one based on their own preferences. However, the FLIGHTS studies (Demberg and Moore 2006;Winterboer and Moore 2007) used a very similar design, and the users in those studies did respond to all forms of tailoring. So the use of a hypothetical user model cannot be the only issue.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations